PENGOLAHAN LIMBAH CAIR PABRIK KELAPA SAWIT KOLAM PENGASAMAN DENGAN MENGGUNAKAN MINERAL ZEOLIT - Ida Nursanti (Universitas Batanghari Jambi, 2014)
So that the palm oil mill wastewater (LCPKS) into organic fertilizer, the required processing which aims to increase the nutrient content and degrade organic matter (dissolved and suspended materials). Alternative processing to do, among others, is to use the chemical processing of mineral zeolite. The study aims to determine the chemical processing techniques LCPKS using zeolite minerals and determine the proper dose of zeolite minerals in order to increase the levels of N, P and K palm oil mill effluent pond acidification and appropriate quality standards of waste. The research was conducted at PT. Sumbertama Nusa Pertiwi Kumpeh District of Hulu Muaro and in the Laboratory, lasted for 3 months. Conducting research using using zeolite minerals clinoptilolite powder 60 mesh types of Gunung Kidul, Yogyakarta. Research using completely randomized design (CRD), with 4 levels of treatment is done by adding the mineral zeolite 0, 5, 10 and 15%, then LCPKS analysis in the laboratory. The results showed that the zeolite 10% on LCPKS Swimming acidification give the levels of N, P, K, which is higher as well as BOD and pH appropriate quality standards of waste. Giving zeolite 15% on LCPKS Swimming Acidification provides the efficiency of adsorption of N, P, and K were higher.Keywords: Fertilizer LCPKS and mineral zeolite